Perlindungan Hukum Data Pribadi Konsumen E-Commerce Berdasarkan Undang-Undang Perlindungan Data Pribadi - Muhammad Ihya Ulumudin; Rosiana Laela Nurul Syahna; Intan Nur Kasanah; Raihan Abdillah (Social Science Academic, 2026)
The rapid growth of the digital economy in Indonesia brings significant challenges in the form of personal data breach risks in e-commerce transactions. This study aims to analyze the legal protection framework for consumers and the responsibility of business actors based on Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The research method used is normative juridical with a statutory and conceptual approach. The results show that the PDP Law provides a strong legal foundation through the regulation of data subject rights, data controller obligations, and strict administrative and criminal sanctions. Legal protection is carried out through preventive mechanisms such as explicit consent (informed consent) and repressive measures in the form of compensation lawsuits and sanction enforcement. However, its effectiveness still faces challenges such as low public digital literacy and the technical readiness of electronic system operators.